2017
DOI: 10.1111/ahg.12209
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Val158Met Catechol‐O‐Methyltransferase Polymorphism and Social Cognitive Functioning in Schizophrenia: Pilot Study

Abstract: The Val158Met catechol-O-methyltransferase (COMT) functional polymorphism may influence social cognitive functioning in patients with schizophrenia. Aspects of social cognition were evaluated with the Facial Expression Recognition Test, the Voice Emotion Recognition Test, and the Reading the Mind in the Eyes Test. The Short Recognition Memory Test for Faces was used as a control measure. The Schedule for the Assessment of Negative Symptoms, Schedule for the Assessment of Positive Symptoms, and Beck Depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 65 publications
0
6
0
1
Order By: Relevance
“…However, to date the effect of the COMT gene on SC has not been sufficiently investigated in SSD and in ASD. Indeed, to date few, spare and contrasting results are available since COMT gene was investigated primarily in SSD and negative associations often has been provided (150,151).…”
Section: Molecular Biomarkers Of Social Cognitionmentioning
confidence: 99%
“…However, to date the effect of the COMT gene on SC has not been sufficiently investigated in SSD and in ASD. Indeed, to date few, spare and contrasting results are available since COMT gene was investigated primarily in SSD and negative associations often has been provided (150,151).…”
Section: Molecular Biomarkers Of Social Cognitionmentioning
confidence: 99%
“…Babovic et al (2008) showed that COMT regulates working memory, as heterozygous mutant mice for this gene had the worst performances in cognitive tasks such as object recognition. This gene is involved in the regulation of affective states (Smolka et al, 2005) and in emotional face processing as well (Tylec, Jeleniewicz, Mortimer, Bednarska-Makaruk, & Kucharska, 2017), leading to significant behavioral and social consequences (Tunbridge, Harrison, & Weinberger, 2006). Bassett, Caluseriu, Weksberg, Young, and Chow (2007) found that COMT Val(158)Met polymorphism affects dopamine metabolism in the frontal cortex, leading to worst outcomes in trials such as trails and olfactory identification, as well as decreased social cognition in 22q11.2 DS individuals with a Met allele single copy.…”
Section: S Oc I Al Cog Ni Ti On R El a Ti Onsh I P S Wi Th Sp E Ci mentioning
confidence: 99%
“…Daar is aangetoon dat KOMT werkende geheue reguleer (Babovic et al 2008). Hierdie geen reguleer ook die affektiewe toestand en emosionele gesigprosessering (Smolka et al 2005;Tylec et al 2017).…”
Section: Komtunclassified